Performance of Photovoltaic as Pump Drive for Alternator Characteristic Monitoring System - Herlambang, Yusuf Dewantoro (Politeknik Negeri Semarang, 2023)
The objectives of this research to generate electrical energy by making photovoltaic which utilizes the potential of solar radiation sources to drive the pump. There are 2 monocrystalline solar panels installed with a capacity of 100 Wp. Installation of solar panels at an angle of 7 ° based on geographic location in the Tambakboyo, Ambarawa, -7.263239